Mass receptiveness to unconstrained emergency legislation during crisis: survey experiment in pandemic-era Japan - Harunobu Saijo; Charles Crabtree (Humanities & Social Sciences Communications)
Abstract To what extent does government messaging influence the willingness of citizens to accept constitutional amendments that empower the executive during crisis? Leaders trying to increase their power often attempt to mobilize public opinion for emergency legislation by emphasizing institutional constraints and crisis severity. To test the extent to which the public is swayed by such rhetoric, a vignette survey experiment was conducted with a national sample of 2569 Japanese during the COVID-19 pandemic. The experiment asks respondents to consider the tradeoff between executive power and their own safety, in a realistic setting. We find robust null effects, suggesting that such messaging does little to sway respondents.